Andragogy and pedagogy learning model preference among undergraduate students - Md. Noora, Norah (Elsevier B.V., 2012)
This paper reports on a research project that investigated the pedagogical and/or andragogical orientation preferred by undergraduate student in one of the Higher Institution in Malaysia. To gather the data, questionnaires were distributed among 323 undergraduate students who took the Introduction to Programming Language course and descriptive analyses have been conducted. In order to validate the data, a qualitative data from interview were gathered to be triangulated. These findings have implications for educators involved in designing online learning applications and will be used to develop a prototype of individualized online learning environment based on the pedagogy and andragogy as its foundational model.